An Investigation into ELT Students’ Academic Achievement and Their Use of Language Learning Strategies Across Gender Groups - Özyılmaz, Özlem (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: This study intended to investigate whether there is a significant mean difference in academic achievement across gender groups, to find out the difference in strategy use between genders, and to reveal the link between strategy use and academic achievement. 90 students (51 female, 39 male) from the Department of English Language Teaching at Eastern Mediterranean University participated in the study. Firstly, 90 students’ GPA and CGPA scores were obtained to see whether there is a significant mean difference in academic achievement across gender groups. Then, in order to find out language learning strategy types used by gender groups, a Turkish version of Strategy Inventory for Language Learning (SILL) by Cesur and Fer (2007) was given to the students. The instrument is based on Oxford’s (1990) classification of the language learning strategies, which is composed of 50 items in six subscales. The data were analyzed through SPSS (15.0) for Windows. A series of t-tests was used. The findings of the study revealed that there is a significant mean difference in academic achievement across gender groups. Females are more successful than males. However, although male students employ more LLS than female students, there is no significant mean difference between strategy use and academic achievement. Keywords: Gender, Language, Language Learning, Language Learning Strategies, Academic Achievement. ………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu çalışma, akademik başarıda cinsiyet bağlamında anlamlı bir farklılık olup olmadığını, ve farklı cinsiyet grupları tarafından kullanılan dil öğrenme stratejilerini tespit edip bu durumun İngiliz Dili Eğitimi Bölümü’ndeki öğrencilerin akademik başarılarıyla bağlantısını belirlemeyi amaçlamaktadır. Çalışmaya Doğu Akdeniz Üniversitesi İngiliz Dili Eğitimi Bölümü’nden 90 öğrenci (51 kız, 39 erkek) katılmıştır. İlk olarak, cinsiyet ve başarı arasındaki ilişkiyi görmek için, 90 öğrencinin dönem sonu not ortalamaları ve genel not ortalamaları belirlenmiştir. Daha sonra, cinsiyet grupları tarafından kullanılan dil öğrenme stratejilerini bulmak için, öğrencilere Cesur ve Fer’in (2007) Türkçeye çevirdiği SILL (Dil Öğrenme Stratejileri Envanteri) verilmiştir. Oxford’un (1990) dil öğrenme stratejileri sınıflandırmasını temel alan araç altı alt kategori içinde 50 madde içermektedir. Veriler, SPSS (15.0) programında analiz edilmiştir. Bir dizi t-test yöntemi uygulanmıştır. Çalışma sonunda, cinsiyet grupları ve akademik başarı arasında anlamlı bir farklılık bulunmuştur. Kızların erkeklerden daha başarılı olduğu ortaya çıkmıştır. Ancak, erkeklerin kızlardan daha fazla dil öğrenme stratejisi kullandıklarının tespit edilmesine rağmen, akademik başarı ve strateji kullanımı arasında anlamlı bir fark bulunmamıştır. Anahtar Kelimeler: Cinsiyet, Dil, Dil Öğrenme, Dil Öğrenme Stratejileri, Akademik Başarı.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2012. Supervisor: Prof. Dr. Necdet Osam.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching - Learning Strategies; Gender - Language - Language Learning - Language Learning Strategies - Academic Achievement